Leveraging an Empire : Settler Colonialism and the Legalities of Citizenship in the Pacific Northwest - Tyler, Jacki Hedlund (Book collections on Project MUSE., 2021)
"Leveraging an Empire examines the process of settler colonialism in the developing region of Oregon through an evaluation of Oregon's exclusionary laws between the years 1841 and 1859"--